The Influence of Work Discipline, Work-Life Balance, and Burnout on Employee Performance at CV Enam Putera Palembang - Muhammad Nurizky Alfi (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
Employee performance is a crucial factor in organizational success, particularly in construction companies, which are required to complete projects on time, with quality, and efficiently. The decline in performance at CV Enam Putera Palembang indicates the need to examine the influence of work discipline, work-life balance, and burnout on employee performance. This research is based on the concepts of Human Resource Management and Spillover Theory, which explain that work experience can have both positive and negative impacts on individual productivity. The study used a quantitative approach with a survey method of 71 employees selected through a saturation sampling technique. Data were collected using a questionnaire and analyzed using multiple linear regression using IBM SPSS Statistics, including validity, reliability, classical assumptions, t-tests, F-tests, and coefficients of determination. The results showed that work discipline and work-life balance had a positive and significant effect on employee performance, while burnout had a negative and significant effect. Simultaneously, all three variables significantly influenced performance, with work discipline being the most dominant variable. These findings suggest that improving performance requires strengthening work discipline, supporting work-life balance, and effectively managing burnout